New insights in the interaction of FGF/FGFR and steroid receptor signaling in breast cancer - Perez, Cecilia (2022)
Luminal breast cancer (BrCa) has a favorable prognosis compared with other tumor subtypes. However, with time, tumors may evolve and lead to disease progression; thus, there is a great interest in unraveling the mechanisms that drive tumor metastasis and endocrine resistance. In this review, we focus on one of the many pathways that have been involved in tumor progression, the fibroblast growth factor/fibroblast growth factor receptor (FGFR) axis. We emphasize in data obtained from in vivo experimental models that we believe that in luminal BrCa, tumor growth relies in a crosstalk with the stromal tissue. We revisited the studies that illustrate the interaction between hormone receptors and FGFR. We also highlight the most frequent alterations found in BrCa cell lines and provide a short review on the trials that use FGFR inhibitors in combination with endocrine therapies. Analysis of these data suggests there are many players involved in this pathway that might be also targeted to decrease FGF signaling, in addition to specific FGFR inhibitors that may be exploited to increase their efficacy.